ANALYSIS OF ANTIOXIDANT CAPACITY AND GLUCOSE LEVEL OF BREADFRUIT LEAVES FUNCTIONAL DRINKS TREATED WITH DIFFERENT RATIO OF SWEETENERS - Devi, Mazarina; Wibowotomo, Budi; Soekopitojo, Soenar (Institut Pariwisata dan Bisnis Internasional, 2019)
Efforts to lower blood sugar levels for diabetes mellitus patients can take by consuming a popular functional drinks which has been added by herbal ingredients such as breadfruit leaves. The aim of this research is to observe the effect of addition three-types of sweetener (aspartame, acesulfam k, and sorbitol) in different ratio (50%: 25%: 25%, 25%: 50%: 25%, 25%: 25%: 50%) to the antioxidant capacity and glucose level of functional drinks made from breadfruit leaves, as well as its number of calories and variety sensory tests (sour taste, sweetness and texture). The experimental design used a Completely Randomized Design with three replications. This study also employs 35 panellists to produce organoleptic quality data in two repetitions. All collected data were then analyzed using ANOVA test followed by DMRT test. Results showed that the highest antioxidant capacity was obtained by ratio 25%: 25%: 50% of aspartame, acesulfam k, and sorbitol with IC50 value of 64,717 ppm. Meanwhile the lowest glucose level was resulted by ratio 50%: 25%: 25% of aspartame, acesulfam k, and sorbitol in value of 25.53 g/100g. The highest number of calorie was produced by ratio 25%: 25%: 50% of aspartame, acesulfam k, and sorbitol with a value of 126.44 cal. / 100gr. Whereas, the most preferred formulas of breadfruit drink formulas are found in ratio 25%: 25%: 50% of aspartame, acesulfam k, and sorbitol.